The secret messenger - Robotham, Mandy (Avon, 2020)
"Venice, 1943: The world is at war, and Stella Jilani is leading a double life. By day she works in the lion's den as a typist for the Reich; by night, she risks her life as a messenger for the Italian resistance. Against all odds, Stella must impart Nazi secrets, smuggle essential supplies and produce an underground newspaper on her beloved typewriter .But when German commander General Breugal becomes suspicious, it seems he will stop at nothing to find the mole, and Stella knows her future could be in jeopardy... London, 2017: Years later, Luisa Belmont finds a mysterious old typewriter in her attic. Determined to find out who it belonged to, Luisa delves into the past and uncovers a story of fierce love, unimaginable sacrifice and, ultimately, the worst kind of betrayal... Set between German-occupied 1940s Venice and modern-day London, this is a fascinating tale of the bravery of everyday women in the darkest corners of WWII." -- Provided by publisher.